1998
DOI: 10.1099/0022-1317-79-12-2957
|View full text |Cite
|
Sign up to set email alerts
|

Two domains of the Borna disease virus p40 protein are required for interaction with the p23 protein.

Abstract: Borna disease virus (BDV) has five major open reading frames, which encode the proteins p40, p23, gp18, p57 and p190. By analogy with other negative-strand RNA viruses, p40 is a putative nucleoprotein and p23 is a putative phosphoprotein. These proteins are known to form com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…It is likeliest that the cytoplasmic distribution of the P modifies the expression level of this protein in the nucleus, resulting in the suppression of viral transcription and replication. Furthermore, intracellular movement of P may also affect the movement of BDV RNPs in infected cells, because P directly interacts with essential components of RNP, such as N, X, and L (1,14,40,45). The retention of P in the cytoplasm could result in prevention of the reimport of the newly synthesized viral RNPs to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likeliest that the cytoplasmic distribution of the P modifies the expression level of this protein in the nucleus, resulting in the suppression of viral transcription and replication. Furthermore, intracellular movement of P may also affect the movement of BDV RNPs in infected cells, because P directly interacts with essential components of RNP, such as N, X, and L (1,14,40,45). The retention of P in the cytoplasm could result in prevention of the reimport of the newly synthesized viral RNPs to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the alteration of subcellular localization of BDV proteins, we examined the intracellular localization of P, because this protein shows clear nuclear localization activity and is known to directly bind to all other components of the viral RNP (1,14,40,45). We demonstrate here that the interaction with X inhibits nuclear localization of the BDV P. Transient-transfection analysis with a cDNA clone corresponding a bicistronic 0.8-kb mRNA that expresses both X and P revealed that P efficiently localizes in the cytoplasm only when X is expressed in the cells.…”
mentioning
confidence: 99%
“…Association of N with viral RNA might induce a conformational change in N, which in turn might expose a binding site for the P⅐L complex. In this context, it is of interest to note that two independent binding sites for P have been described (31).…”
Section: Discussionmentioning
confidence: 99%
“…The various ORF3-coding regions were inserted into the EcoRI and XhoI sites of the pGEX-5T plasmid (Stratagene) for expression in Escherichia coli BL21 (DE3) as described previously (Timmusk et al, 2006). Briefly, for the GST pulldown studies, the PCV2 full-length ORF3 proteins from SG1, SG2, SG3, the full-length ORF3 protein from PCV1 and the partial ORF3 from PCV1, as well as negative control proteins, were expressed by using the pGEX-5T system (Berg et al, 1998). All proteins were expressed in E. coli BL21 (DE3) and induced with 1 mM IPTG at room temperature overnight.…”
mentioning
confidence: 99%
“…The two identical sets of samples were then analysed on two parallel SDS-PAGE gels. Unrelated proteins (ORF2 of PCV2 and bornavirus B33 protein) fused with GST (Timmusk et al, 2006;Berg et al, 1998) were used as negative controls. One of the gels was dried and the binding of ORF3 from various PCV isolates to poRGS16 was measured by phosphoimager analysis.…”
mentioning
confidence: 99%